Economic research and the development of economic science and public policy - National Bureau of Economic Research (New York : National Bureau of Economic Research, 1946)
This research comprises of twelve papers ranging from a projection of economic science in the future to a moving plea for scientific integrity.
Twelve papers presented at the twenty-fifth anniversary meeting of the National Bureau of Economic Research, June 6 and 7, 1946, New York.
Includes bibliographical footnotes and index.
ne 12/04/2019
Loans
Keywords: Economics